EFFECT OF VARYING NDF LEVELS ON PRODUCTIVE PERFORMANCE IN LACTATING NILI RAVI BUFFALOES - S. Ahmed; M. A. Jabbar; A. Khalique; K. Javed; Saima; N. Ahmed; F. Shahzad; M. Fiaz (Journal of Animal and Plant Sciences, 2014)
The aim of study was to evaluate the effect of varying levels of dietary NDF on voluntary feed intake, nutrient digestibility, milk production and composition in early lactating (n=25) Nili Ravi buffaloes. Five groups with five animals in each, under completely randomized design were fed A, B, C, D and E rations which were iso nitrogenous and isocaloric based on NDF levels 23, 28, 33, 38 and 43%, respectively. Nutrient intake and nutrient digestibility differ (P<0.001) significantly among the dietary groups. Dry matter (DM), crude protein (CP) and neutral detergent fibre (NDF) intake (kg/d) were found highest in animals fed diet C (14.31±0.05), C (1.86±0.006) and E (5.52±0.018) respectively than those on the other four treatments. Whereas, DM, CP and NDF digestibility percentage were observed the highest in the group B (62.88±1.04), B (51.00±0.57) and C (64.4±0.99) respectively, as compared to others. The 4% fat corrected milk (kg/day) production was significantly (P<0.001) higher in group A (11.23±0.15) as compared to others. In term of milk composition (TS 16.65±0.07%, fat 7.01±0.04%, milk protein 3.78±0.02% and milk lactose 5.04±0.02%) were observed the highest in group D (38% NDF). Hence it is concluded that 33% NDF level is better in terms of NDF digestibility and 23%NDF in terms of 4%FCM production in early lactating Nili Ravi buffaloes.
Keywords: Nili Ravi buffaloes; NDF; ADF; voluntary intake; weight gain